Peningkatan Kemampuan Masyarakat Bidang Teknologi Informasi - Hasan, Sholeh; Marlina, Marlina; Putri, Andewi Yunita; Dewi, Diska Puspa (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STKIP Nurul Huda, 2021)
In the village context, technology problems are still common. Among those who are often encountered is that they do not have the awareness, knowledge and skills related to information technology and digitalization that are developing today. There needs to be a special institution to supply knowledge and skills so that people can keep up with technological developments. On that basis, through the ALINI Course and Training Institute, the author took a role in increasing the human resource capacity of the Sriwangi village community and its surroundings, which was attended by 30 participants. The training is carried out in a structured and scheduled manner according to the agenda prepared by the organizer with a duration of three months from January 2021 to March 2021. The evaluation results showed an increase in the participants' ability to recognize and operate computers. It is hoped that after this training they will be able to apply their abilities to enter the real world according to their respective fields. The output of this dedication is to provide more support or even as a reference material for the author to publish in the Indonesian Journal of Serving.